Pelatihan pembuatan pupuk bokasi dari limbah kotoran ayam untuk meningkatkan kualitas air media budidaya lele Dumbo di Kelurahan Mentangor, Kecamatan Tenayan Raya, Kotamadya Pekanbaru Provinsi Riau - Mulyadi Mulyadi; Iesje Lukistyowati; Niken Ayu Pamukas; Adelina Adelina (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
Chicken manure is an organic material that is abundant in Mentangor Village which has been used as fertilizer when fertilizing ponds, however the continuous use of fertilizers can reduce the quality of the bottom soil and pond water. One of the technological innovations to improve the quality of chicken manure is fermentation using EM4 to produce bokashi fertilizer. Bokashi fertilizer can increase the abundance of phytoplankton and zooplankton which are useful as natural fish food so that they can reduce the use of artificial feed, which in turn can reduce the operational costs of fish farming. Community service activities are carried out for the purpose of innovating knowledge and skills of fish farmers regarding techniques for making bokashi fertilizer from chicken manure and techniques for making fish feed in the form of pellets to increase cultivated fish production. This activity is carried out by lecturing, discussion and practice methods, which involve fish cultivator groups and Kukerta students. The results of community service activities show the high enthusiasm of farmers towards the activities carried out, resulting in increased knowledge, insight and skills of farmer groups. Thus, fish farming activities can be carried out by farmers by reducing operational costs for pond management and provision of feed so as to produce high fish production and increase the income and welfare of farmer groups.